AuGe surface plasmon enhances photoluminescence of the InAs/GaAs bilayer quantum dot heterostructure. Issue 32 (14th March 2016) - Pandey, Sushil Kumar; Tyagi, Lavi; Shete, Pranav; Ghadi, Hemant; Rawool, Harshal; Murkute, Poonam; Chakrabarti, Subhananda
Abstract : We report an improvement in the photoluminescence of a GaAs-capped InAs/GaAs bilayer quantum dot (QD) heterostructure by AuGe nanoparticle deposition on the surface of a thin capped layer. Abstract : We report an improvement in the photoluminescence of a GaAs-capped InAs/GaAs bilayer quantum dot (QD) heterostructure by AuGe nanoparticle deposition on the surface of a thin capped layer. Scanning electron microscopy confirmed the formation of AuGe nanoparticles on the surface at temperatures ranging from 300 to 700 °C. Optical absorption spectroscopy revealed the plasmon resonance peak of AuGe nanoparticles at around 670 nm for the sample annealed at 300 °C, confirming the presence of the plasmonic effect. Raman spectroscopy revealed a QD phonon peak at ∼238.5 cm −1 for the sample annealed at 300 °C, indicating InAs QDs in the heterostructure. Compared to the uncovered sample, enhancements were observed in the PL spectra of the AuGe-deposited samples annealed at 300 °C and 400 °C (with enhancement factors of 2.58 and 2.18, respectively). The observed enhancement is attributed to photon trapping by scattering from the cross section of the dipole radiation field. Increasing the annealing temperature from 300 °C to 700 °C blue-shifted the photoluminescence peaks at 18 K because of In/Ga inter-diffusion. A decrease in activation energy was observed with the increase in annealing temperature from 300 °C to 700 °C, attributed to poor confinement potential and high electron concentration at the sample surface. Our findings contribute to the realization of high-efficiency plasmonic-based InAs QD detectors for optical communication in the 1300 nm optical window.